A sprinkle of sorcery - Harrison, Michelle 1979- (Simon & Schuster Children's, 2020)
The family curse has been lifted and the Widdershins sisters: Betty, Fliss and Charlie are free to leave the misty prison isle of Crowstone. But when a mysterious girl arrives at the Poacher's Pocket with a pocketful of hagstones and accompanied by a will-o'-the-wisp, it seems another adventure has landed on their doorstep. And when Charlie goes missing, it's up to Betty and Fliss to journey through misty marches, past wisp catchers and on to a secret island that doesn't exist on any map..
"A missing sister. A magical island, and..." --Front cover
Fortsetzung von: A pinch of magic
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Suche; Insel; Schwester; Fantastischer Roman; Vermisstes Kind; Magie; Children's stories; Sisters / Juvenile fiction; Magic / Juvenile fiction; Missing persons / Juvenile fiction; Quests (Expeditions) / Juvenile fiction; Islands / Juvenile fiction; Islands; Magic; Missing persons; Quests (Expeditions); Sisters; Fantasy fiction; Fiction; Juvenile works; Paranormal fiction; Kinderbuch